Perancangan Sistem Kontrol Propulsi Hibrida Kapal Trimaran Berbasis Fuzzy Logic - Aldoko, Fajar Surya Muhammad; Kurniawan, Edi; Amrullah, Romanda Annas; Nurdiansari, Henna; Sandi, Wulan Marlia (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2025)
This study presents the design and implementation of a hybrid propulsion control system for a trimaran vessel using fuzzy logic. The system integrates a Brushless DC (BLDC) motor and an internal combustion engine, controlled by STM32 and ESP32 microcontrollers, with sensors for speed and current monitoring. The fuzzy logic algorithm was developed with two input variables—speed error and delta error—and one output variable for motor control. Experimental testing was conducted on a trimaran prototype in river conditions to evaluate system performance. The results show that, without fuzzy logic, the vessel’s speed fluctuated significantly, deviating from the reference set point. In contrast, with fuzzy logic control, the vessel maintained a more stable speed, achieving an average error of less than 5%. This demonstrates that fuzzy logic can effectively address the non-linear characteristics of hybrid propulsion systems, providing adaptive control that enhances speed stability and energy efficiency.